ANALISIS NILAI TAMBAH DAN COST VOLUME PROFIT USAHA PENGOLAHAN KOPI SAHABAT DI KOTA LUBUK LINGGAU SUMATERA SELATAN - Een Subaeni; Redy Badrudin; Reswita Reswita (JURNAL AGRIBISNIS TERPADU, 2017)
The Sahabat coffee processing business that process coffee beans into ground coffee and durian coffee. The Sahabat coffee processing business has a promising business opportunities in an effort to increase value added and profits. This study aims to analyze the added value and Cost Volume Profit including Net Income, Break Even Point, Profitability and Degree of Operating Laverage in Sahabat coffee processing business. The method of analysis used is the value added analysis of Hayami method and Cost Volume Profit method. The results showed that the valueadded obtained from the processing of coffee beans to ground coffee 250gr and 1 kgis 9,83% and 12,46%, while durian coffee 200 gr and 30 gr is64,99% and 35,57%.The result of analysis cost profit volume shows that net income obtained by coffee processing business from ground coffee 250 gr and 1 kg is Rp.3.259.902/month and Rp.4.732.781/month, while durian coffee 200 gr and 30 gr is Rp.4.853.798/month and Rp.1.722.111/month. The break even point of ground coffee 250 gr and 1 kg is 3.309 sashet/month and 697sashet/month, while break even point of durian coffee 200 gr and 30 gr is39 sashet/month and 770sashet/month. Profitability of ground coffee 250 gr and 1 kg is 4,35% and 6,01%, while durian coffee is 42,69% and 20,15% and Degre of Operating Laverage ground coffee 250 gr and 1 kg is 1,77and 1,59, while durian coffee 200 gr and 30 gr is 1.15 and 1,69.